Exploring the Potentials of Betaine Supplementation in Poultry and Pig: A Review - Mishra, Alok (Indian Journal of Animal Nutrition, 2021)
The present review explores the nutritional and performance boosting functions of betaine in poultry and pig ration as a feed additive. Betaine, a trimethyl derivative of glycine is a normal metabolite in many plant and animal tissues. In all the animals, betaine is produced by oxidation of choline or supplied through feed. Its characteristics chemical structure makes betaine a dipolar zwitterion, conferring it osmoprotective and methyl donating properties. Over the past decades, numerous studies have investigated and published the favorable effects of betaine on performance in different animal species. Betaine is involved in transmethylation reactions for the synthesis of several metabolically active substances like creatine, carnitine etc. Also, it has shown evidence to increasing nutrient utilization, digestibility and methionine availability. Boosting immune status and reducing oxidative or heat stress are also some of the important functions of betaine. Most of the researches have specifically studied the growth promoting, carcass modulating, immune boosting or stress reducing properties of betaine in different species. Literature covering on different benefits of betaine as an essential feed supplement is not yet abundant. As both poultry and pig are important species of domesticated animals, betaine can be a better and cheaper, alternative feed supplement for enhancing the nutrient utilization and performance of poultry and pig. Therefore, an attempts have been made to delineate the functional effects of supplementary betaine in poultry and pig.